The Little Years - Mighton, John (Playwrights Canada Press, 2013)
Growing up in the 1950s, Kate is fascinated by time and space, interests dismissed as unbecoming to a young woman of her time. While her brother William achieves literary renown, her family struggles to reach the brilliant Kate as she grows from precocious teen to troubled woman.